Self-Funded Social Impact Investment: An Interdisciplinary Analysis of the Sardex Mutual Credit System. Issue 2 (4th May 2017) - Motta, Wallis; Dini, Paolo; Sartori, Laura
ABSTRACT: Sardex is a B2B electronic complementary currency and mutual credit system. It allows private funding to be endogenously generated within a geographically limited socio-economic context, rather than injected from exogenous sources, leading to a greater level of positive social impact. Sardex promotes stable and constructive integration of market activity with democratic institutions and socio-cultural values, and is hence identified with sustainable development. This paper presents a case study based on 29 semi-structured in-depth interviews of Sardex members. By drawing on monetary theory, sociology and anthropology, the paper argues that Sardex implements a form of self-funded social impact investment.